(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
There is a severe lack of research on the heat transfer mechanisms for various populations, with most studies primarily concentrating on adults. This study aimed to investigate the difference in the convective heat transfer coefficient (h_c) of the whole and individual body parts between infant and adult under ventilation. A numerical model for heat transfer between the human body and the environment was developed and validated against experiments involving a baby thermal manikin. The temperature and airflow fields surrounding the human body and the value of h_c were simulated under seven air velocities ranging from 0.1 m/s to 2.5 m/s. The results indicated that, under natural ventilation, the overall h_c for infants and adults was 4.82 W/m^2·K and 4.29 W/m^2·K, respectively. Infants exhibited higher regional h_c values at their surface than adults, especially on their hands and feet. This discrepancy was more pronounced as the air velocity increased. Furthermore, regression equations were developed for the two body sizes to establish the connection between h_c and air velocity. These findings contribute to a better understanding of the complex interplay between body size and convective heat transfer, providing fundamental data for enhancing the accuracy of infant thermal response predictions by incorporating more precise boundary conditions.